Verification of Fracture Reorientation and Analysis of Influence Factors in Multiple Fracturing Treatment. (25th September 2020) - Lu, Mingjing; Su, Yuliang; Gutierrez, Marte; Zhan, Yaohua; Chen, Kai; Zheng, Bintao
Abstract : A fracture will be initiated and propagated along the direction of maximum horizontal stress in fracturing treatment; however, in refracturing stimulation, the new fracture may be initiated and propagated along a different direction from the initial one. This is defined as a fracture reorientation. It is difficult to predict fracture reorientation due to the variation of formation properties after long-term production. To verify the existence of fracture reorientation and analyze its influencing factors in multiple fracturing treatment, experimental and numerical simulations are presented in this paper. Firstly, multiple fracturing stimulation is carried out with a self-assembled large true triaxial apparatus, and the fracture reorientation is successfully induced by changing the injection pressure and initial stresses in multiple fracturing processes. Then, numerical coupled hydromechanical modeling of the actual field production and injection well pattern is performed. In particular, the stress reversal region, which indicates the distance of fracture reorientation, and the factors that influence the reorientation are analyzed. The laboratory experiment and numerical simulation results show that the fracture reoriented angle obtained can be perpendicular to the initial fracture. Stress field and formation pressure are the two main factors that influence the fracture reorientation. With higher pressure differences and lower initial horizontal stress differences, the area in which it is possible to initiate reoriented fracture will be larger. The fractures of wells in the early production stage are hard to reorient due to the high formation and borehole pressure difference, and the fracture reorientation area will be expanded until the pressure difference is low to a certain value. This research result can guide oilfield stimulation treatments.